Learn from the SARS-CoV-2 nucleic acid test to increase the experience of dealing with the “disease X - Yang, Xin; Li, Jinming (BMC infectious diseases, 2025)
RT‒PCR is crucial for screening for epidemic diseases such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, false positives further plague epidemic prevention and control. This study conducted a stratified study on the initial screening Ct values and false positive ratios, providing experience and reference for addressing future "Disease X". Data from 1,255 positive or suspected positive results were obtained from eleven laboratories with seven different reagents. The proportion of false positives was analyzed on the basis of different Ct values among different reagents and various testing institutions. When the Ct values of both target genes in the initial detection were < 30, a false positive was considered a small probability event (≤ 1.72%). However, when the 30 ≤ Ct value was < 35, significant differences were noted (0%, 1.41%, 7.69%, and 9.14%, P < 0.001). When the Ct value of any target gene is > 35, 15.58 - 24.22% of positive results may be false positive. Among the suspected positive samples, 53.23% were false positive according to retesting. After separate sampling, 4 tubes (30 people involved) from 19 tubes (133 people involved) were negative. In summary, different strategies should be adopted according to the different Ct values of primary screening results under pandemic prevention and control conditions, which may provide a better reference for the rapid diagnosis of the next "Disease X".